The dark tower - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2004)
Roland Deschain and his ka-tet have journeyed together and apart, scattered far and wide across multilayered worlds of wheres and whens. The destinies of Roland, Susannah, Jake, Father Callahan, Oy, and Eddie are bound in the Dark Tower itself, which now pulls them ever closer to their own endings and beginnings...and into a maelstrom of emotion, violence, and discovery.